A new two‐stage method for single image rain removal. Issue 2 (15th December 2020) - Zhu, Jian; Liu, Peiyu; Luo, Yu; Ling, Jie; Wu, Enhua
Abstract: Compared with video de‐raining, single image de‐raining is more technically difficult due to the lack of temporally redundant information. This paper proposes a new two‐stage method for single image de‐raining. In the first stage, the authors develop an effective two‐step model to detect the rain streaks by taking pixel intensity, and direction of rain streaks as priors. In the second stage, the rain repair process is performed at the patch level. The authors first define a way to search for similar patches of each patch, and then group the similar patches together to form a matrix. Finally, a low‐rank matrix completion technique is utilized to recover the rain‐stained pixels based on the rain map obtained from the first stage. Compared with several state‐of‐the‐art methods, authors' proposed method is competitive in terms of the abilities of removing rain streaks, and preserving image details.